Safe, Autonomous and Intelligent Vehicles - Yu, Huafeng; Li, Xin.; Murray, Richard M.; Ramesh, S.; Tomlin, Claire J.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book covers the start-of-the-art research and development for the emerging area of autonomous and intelligent systems. In particular, the authors emphasize design and validation methodologies to address the grand challenges related to safety. This book offers a holistic view of a broad range of technical aspects (including perception, localization and navigation, motion control, etc.) and application domains (including automobile, aerospace, etc.), presents major challenges and discusses possible solutions. Provides a single-source guide to the practical challenges in designing autonomous and intelligent systems; Discusses the major challenges related to safety of next-generation autonomous and intelligent systems, given growing complexity and new applications; Describes new design and validation methodologies to address safety issues; Includes technical background to facilitate further research and development.
Introduction -- Statistical Validation of In-Vehicle Machine Learning Systems -- Cyberattack-Resilient Hybrid Switching Controller Design with Application to Unmanned Aircraft System -- Control and Safety of Autonomous Vehicles with Learning-Enabled Components -- AdaStress: Adaptive Stress Testing and Interpretable Analysis of Safety-Critical Systems -- Provably-correct control synthesis for vehicle safety systems -- Reachable Set Estimation and Verification for Neural Network Models of Nonlinear Dynamic Systems -- Adaptation of Human Licensing Examinations to the Certification of Autonomous Systems -- Model-based Software Synthesis for Safety-critical Cyber-Physical Systems -- Compositional Verification for Autonomous Systems with Deep Learning Components -- Index.
Keywords: Electronic circuits; Signal processing; Microprocessors; Computer architecture; Electronic Circuits and Systems; Signal, Speech and Image Processing; Processor Architectures